2008
DOI: 10.1073/pnas.0712324105
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex2 regulates Purkinje cell dendrite morphology and motor coordination

Abstract: The small GTPase Rac controls cell morphology, gene expression, and reactive oxygen species formation. Manipulations of Rac activity levels in the cerebellum result in motor coordination defects, but activators of Rac in the cerebellum are unknown. P-Rex family guanine-nucleotide exchange factors activate Rac. We show here that, whereas P-Rex1 expression within the brain is widespread, P-Rex2 is specifically expressed in the Purkinje neurons of the cerebellum. We have generated P-Rex2 ؊/؊ and P-Rex1 ؊/؊ /PRex2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 40 publications
2
96
0
Order By: Relevance
“…In this project, we assessed the roles of the P-Rex and Vav families in GPCR-dependent neutrophil function to determine potential redundancy or cooperation between them. Previous studies have shown that, of the P-Rex family, PRex1 is highly expressed in neutrophils, whereas P-Rex2 expression is undetectable, suggesting that P-Rex1 is the only P-Rex family member in these cells (22,31). All three Vav isoforms are expressed, however Vav2 is 30-fold less abundant than Vav1 and 120-fold less abundant than Vav3 (25); hence, Vav1 and Vav3 are the major isoforms in mouse neutrophils.…”
Section: Resultsmentioning
confidence: 96%
“…In this project, we assessed the roles of the P-Rex and Vav families in GPCR-dependent neutrophil function to determine potential redundancy or cooperation between them. Previous studies have shown that, of the P-Rex family, PRex1 is highly expressed in neutrophils, whereas P-Rex2 expression is undetectable, suggesting that P-Rex1 is the only P-Rex family member in these cells (22,31). All three Vav isoforms are expressed, however Vav2 is 30-fold less abundant than Vav1 and 120-fold less abundant than Vav3 (25); hence, Vav1 and Vav3 are the major isoforms in mouse neutrophils.…”
Section: Resultsmentioning
confidence: 96%
“…Physiologic relevance of P-Rex proteins P-Rex1 is mainly expressed in peripheral blood leukocytes and in the brain and is also expressed in several other tissues (8,(11)(12)(13)(14). P-Rex2 is widely expressed and is strongly present in skeletal muscle, the small intestine, heart, lung, and placenta, being absent from peripheral blood leukocytes (10,11,13).…”
Section: P-rex Genes and Protein Isoformsmentioning
confidence: 99%
“…P-Rex2 is widely expressed and is strongly present in skeletal muscle, the small intestine, heart, lung, and placenta, being absent from peripheral blood leukocytes (10,11,13). P-Rex1 À/À mice are viable and apparently healthy but have mild neutrophilia (15).…”
Section: P-rex Genes and Protein Isoformsmentioning
confidence: 99%
“…Phosphatidylinositol 3,4,5-trisphosphate Rac exchanger 2 (PREX2) is a 183 kDa protein that activates the small guanosine triphosphatase Rac, and is capable of mediating Rac signaling downstream of G protein-coupled receptors and AKT (10). A previous study demonstrated that PREX2 regulates Purkinje cell dendrite morphology and motor coordination (11), and it has been reported to inhibit the activity of PTEN by binding directly to PTEN via the guanine nucleotide exchange factor domain of PTEN (12). Furthermore, PREX2 may work in combination with a phosphatidylinositol-4,5-bisphosphate 3-kinase (PIP3), catalytic subunit alpha mutant to promote proliferation and transformation of cells, which is growth-factor independent (12).…”
Section: Introductionmentioning
confidence: 99%